ПОСИЛЕННЯ ЕЛЕКТРИЧНОГО ПОЛЯ В ПОЛІЕТИЛЕНОВІЙ ІЗОЛЯЦІЇ СИЛОВИХ КАБЕЛІВ З ДЕФЕКТАМИ - Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2018)
The computer modeling of electric field distribution in the cable polyethylene insulation with defects (porosity along the insulation in radial direction and contamination due to the fault at application of insulation layers during the production process) is carried out. The distributions of volumetric electric force and equivalent tensile stress in the insulation are computed in the case of the contamination. The effect of the defects on electric intensity near the conductor screen (inner semiconducting layer) and the dependence of the distributions and maximum electric intensity on the electric properties of the porous medium, shape of the contamination and its proximity to the cable conductor are revealed. References 11, figures 5.